BPJS Patient's Perception of Service Quality at The Outpatient Department of Panembahan Senopati Bantul Public Hospital - Medina Fitriananda Librianto; Iwan Dewanto; Elsye Maria Rosa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Background: Panembahan Senopati Hospital Bantul as a type B public hospital and a referral hospital for BPJS patients experienced a significant decrease in the number of outpatient visits in 2019. The perception of BPJS participant patients is a benchmark for evaluating the quality of the service that has been provided. This study aims to determine and analyze how is the BPJS patient’s perception of the outpatient department’s service quality using the SERVQUAL theory approach and the factors that influence these perceptions. Methods: This study employs a descriptive-analytic observational method with a cross-sectional design. The purposive sampling strategy was used to choose 217 BPJS patients who met the inclusion and exclusion criteria. A quantitative data type was used, including a Likert-choice questionnaire that was enhanced with essay questionnaire items. The Statistical Product and Service Solutions (SPSS) program version 26 was utilized to analyze the Likert data, and the NVivo12 plus application was used to analyze the essay questionnaire. Result: BPJS patients describe the service quality of the outpatient department at Panembahan Senopati Hospital Bantul as high in all facets of the SERVQUAL quality dimension, including Reliability, Responsiveness, Assurance, Tangibles, and Empathy. Education has a substantial impact on perceptions of Responsiveness (p-Value 0.045), Assurance (p-Value 0.022), and Tangibles (p-Value 0.003). Occupational characteristics have a substantial impact on perceptions of Tangibles (p-Value 0.004) and Total Variables dimensions (p-Value 0.043). Conclusion: The service quality in the outpatient department at Panembahan Senopati Hospital is in the high-quality category. Age and gender factors have no significant effect on service quality perceptions, however, education and occupation have a significant effect on the service quality perceptions. Abstrak: Latar belakang: RSUD Panembahan Senopati Bantul sebagai rumah sakit tipe B milik pemerintah dan sekaligus rumah sakit rujukan pasien BPJS mengalami penurunan signifikan jumlah kunjungan pasien di poliklinik rawat jalan pada tahun 2019. Persepsi pasien peserta BPJS menjadi tolak ukur evaluasi kualitas layanan yang telah diberikan. Penelitian ini bertujuan mengetahui dan menganalisis bagaimana persepsi pasien BPJS terhadap kualitas pelayanan poliklinik menggunakan pendekatan teori SERVQUAL serta faktor – faktor yang mempengaruhi persepsi tersebut. Metode: Jenis penelitian ini adalah observasional deskriptif analitik dengan metode cross sectional. Sampel penelitian sebanyak 217 pasien BPJS yang memenuhi kriteria inklusi dan eksklusi, dengan teknik purposive sampling. Jenis data berupa kuantitatif menggunakan kuesioner pilihan Likert dan diperdalam dengan pertanyaan kuesioner esai. Analisis statistik data menggunakan program Statistical Product and Service Solutions (SPSS) serta analisis kuesioner esai menggunakan program NVivo. Hasil: Kualitas pelayanan poliklinik RSUD Panembahan Senopati Bantul dipersepsikan memiliki kualitas tinggi oleh pasien BPJS pada seluruh aspek dimensi kualitas SERVQUAL yaitu dimensi Keandalan, Daya Tanggap, Jaminan, Bukti Langsung, dan Empati. Faktor pendidikan memiliki pengaruh signifikan terhadap persepsi pada dimensi Daya Tanggap (p-Value 0,045), Jaminan (p-Value 0,022), dan Bukti Langsung (p-Value 0,003). Faktor pekerjaan memiliki pengaruh signifikan terhadap persepsi pada dimensi Bukti Langsung (p-Value 0,004) dan Total Variabel (p-Value 0,043). Kesimpulan: Persepsi kualitas pelayanan di poliklinik rawat jalan RSUD Panembahan Senopati Bantul berada pada kategori kualitas tinggi. Faktor usia dan jenis kelamin tidak berpengaruh signifikan terhadap persepsi kualitas layanan, sedangkan faktor pendidikan dan pekerjaan berpengaruh signifikan terhadap persepsi kualitas pelayanan poliklinik.